2014
DOI: 10.5267/j.msl.2014.4.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of atmospheric elements on emotions, perceived value and behavioral intentions

Abstract: This research proposes a comprehensive integrated model, which investigates the relationships between atmospheric elements, emotions, perceived value and behavioral intentions. Data collected through customers of three Salian chain stores by using stratified random sampling method and the analysis uses 390 questionnaires to collect the information. Structural equations modeling by using LISREL was performed to empirically test the relationships between the constructs of this research. Results show that ambienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
4
10
0
Order By: Relevance
“…This influence is lower than the direct influence between store image and repurchase without going through emotional variables. The results of a similar study were found in the study of Bigdeli et al (2014). The existence of a good store image from aspects of the atmosphere, interaction, and good arrangement will increase the emotions of the customer.…”
Section: Structural Model Compatibility Test Resultssupporting
confidence: 74%
“…This influence is lower than the direct influence between store image and repurchase without going through emotional variables. The results of a similar study were found in the study of Bigdeli et al (2014). The existence of a good store image from aspects of the atmosphere, interaction, and good arrangement will increase the emotions of the customer.…”
Section: Structural Model Compatibility Test Resultssupporting
confidence: 74%
“…This result indicates that when customers feel higher levels of pleasure, they become more likely to convey higher intentions to revisit the restaurant and to recommend it to their friends. This result conforms to the findings of several similar empirical studies (Ryu & Jang, 2007;Ali & Amin, 2014;Bigdeli & Bigdeli, 2014). The results of Sweeney and Wyber (2002) for instance confirmed a positive association between the affective states of customers and their behavioural intentions.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…In the M-R model, emotion states fall into three basic elements involving: pleasure; arousal; and dominance (known as PAD states). Conceptual insights and observed evidences reported dominance as a non-significant affective state in predicting individual behaviour in business environments, where much of the affective responses are mainly limited to pleasure and arousal (Ryu & Jang, 2007;Ali & Amin, 2014;Bigdeli & Bigdeli, 2014;Hermawan & Yusran, 2015;Morrison et al, 2011;and Simanjuntak et al, 2020). In accordance with this, our study will adopt only pleasure and arousal as major affective organism states.…”
Section: Fig 1 One-step Parallel Mediation Modelsupporting
confidence: 67%
See 2 more Smart Citations